Cubitus Varus Following Pediatric Supracondylar Humeral Fracture: A Narrative Review of Pathogenesis, Diagnosis, and Contemporary Management - Elyana Tabina Astariyati; Dinni Anisa Ishabil; Ni Putu Ayu Sanchita Ardyani; Adhwa Renata; Juan Maolidi; Noor Hidayani Rezky Mulya; Anom Josafat (Jurnal Biologi Tropis, 2026)
Cubitus varus, or gunstock deformity, is a three-dimensional post-traumatic elbow deformity most commonly associated with malunion after pediatric supracondylar humeral fracture. The deformity combines coronal varus, sagittal hyperextension, and internal rotation and may be associated with pain, motion limitation, instability, ulnar nerve symptoms, and cosmetic concerns. This narrative review synthesizes international peer-reviewed evidence published from 2016 through August 2026 on pathogenesis, clinical assessment, imaging, and contemporary management. Literature was identified through PubMed, ScienceDirect, SpringerLink, Frontiers, and Google Scholar using terms related to cubitus varus, supracondylar humeral fracture, distal humeral malunion, corrective osteotomy, guided growth, and three-dimensional planning. Recent evidence supports malunion after inadequate reduction or loss of alignment as the principal mechanism, while the limited remodeling capacity of coronal and rotational deformity contributes to persistence. Diagnosis requires comparison with the contralateral elbow, range-of-motion and neurovascular examination, stability assessment, and radiographic evaluation, including humerus-elbow-wrist and Baumann angles. Observation is appropriate for selected mild asymptomatic deformities. Symptomatic, functionally limiting, unstable, neurologically complicated, severe, or unacceptable cosmetic deformities are generally treated with distal humeral corrective osteotomy. Contemporary techniques include lateral closing-wedge, dome, step-cut, reverse-V, and multiplanar osteotomies. Three-dimensional planning and patient-specific guides improve the accuracy of complex correction, while guided growth is an option for carefully selected skeletally immature children. Treatment should be individualized according to deformity pattern, symptoms, skeletal maturity, and surgical expertise.